The Analysis of Critical Thinking Skill of Version P21 in Solving the Problems of Two Dimensional Arithmetic Derived from the Implementation of Guided Discovery Learning - Robi, Afif Alfa; ., Hobri; ., Dafik (International Journal of Scientific Research and Management (IJSRM), 2018)
This study aims to analyze the critical thinking skills of P21 students in solving Arithmetic Two Dimensional problems through the application of Guided Discovery Learning. GDL is a learning process that occurs when students are not presented  with material in final form but learners are expected to organize their own material with guidance from educators if needed. Implementation of GDL in learning process is expected to improve students' thinking ability, especially critical thinking ability version P21. According to P21, in the 21st century, every individual is required to have 4C's skills in order to compete globally and one of 4C's skills is critical thinking. By having these skills, learners are expected to achieve success in life and work. The subjects of this study are discrete mathematics class students, as many as 64 students. Research steps are by providing initial knowledge of Two Dimensional Arithmetic materials through GDL method and Student Worksheet (LKM) then at the end of student learning work on Test Mastery of Teaching Materials (TPBA). The test results are then analyzed using the P21 critical thinking indicator that is reasoned effectively, using a system of thinking, making judgments and decisions. From the analysis result of Teaching Material Mastery Test obtained data about critical thinking level of students, in class A there are 25 students being in very high category (level 4), 10 students are in high category (level 3) and 9 students are in medium category (level 2). While in class C there are 22 students being in very high category (level 4), 4 students are in high category (level 3) and 4 students are in medium category (level 2). The study also produced a two dimensional arithmetic monograph. From the results of this study can be concluded that the application of GDL has a positive effect in developing students' critical thinking skills in solving two-dimensional arithmetic problems.